Future of Irrigated Agriculture - Vaux Jr., Henry J.; Adams, Richard M.; Ayer, Harry W.; Hamilton, Joel R.; Howitt, Richard E.; Lacewell, Ronald; Supalla, Ray; Whittlesey, Norman (Council for Agricultural Science and Technology (CAST), 1996)
Farmers irrigating in the western United States face a host of changing circumstances that will require innovations and new adaptations to ensure continued prosperity.